Іcторія, особливості архітектури та реставрації дзвіниці Троїцько-Іллінського монастиря - Миколайко, Т. (Сiверянський лiтопис, 2019)
У статті йдеться про історію будівництва дзвіниці Троїцько-Іллінського монастиря у Чернігові, характеризуються її архітектурні особливості та подано історію ремонтів і реставрації в різні часи. In this article talks about the history of the construction of the bell tower of the Trinity- Illinskyi monastery in Chernihiv and its architectural peculiarities are described. The bell tower was built in the 70’s of the XVIIIth century in the baroque style by archimandrite Ioil (Bykovsky). The surname of the architect – the builder is unknown, according to some evidences, the design drawings of Johan Schöder, the author of the bell tower of the Kyiv- Pechersk Lavra were used. Located in the ensemble of the monastery, the bell tower became the main landmark for a traveler from Kiev, Nizhyn etc. The brick construction, five tiered, in the plan is square and has a height of 57.96 m. Facades on each tier of four corners are decorated with columns, in the first tier of 6 columns at each corner, on the third and fourth to 5. The fifth tier ends with a dome crowned with a cross. The construction is decorated with moldings and its refinement is complemented by metal lattices and vases on tiers. The bell tower is painted in two colors: moldings in white, and planes in yellow. The construction of the bell tower was repeatedly restored. And the first repair was carried out immediately after building, because in 1778 its top was burned out by lightning. The bell tower was renovated in the 90’s of the XVIIIth century for money allocated by general M. Krechetnikov. At the beginning of the XIXth century on the bell tower was arranged the first in the city street clock with a fight from siberian iron. Unfortunately, until nowadays it hasn’t survived. In the postwar period, the bell tower was restored twice: for the first time – 1956–1960’s, and for the second time – 1981–1982’s. Then the masonry and moldings destroyed in many places, cast-iron decorative vases, plastering and painting were restored.